Supply Chain Integration of the Health Supplement Industry in Malaysia: A Case Study of Bioalpha Holdings Berhad - Hon, Tian Kok (2024)
This thesis explores the effects of Supply Chain Integration (SCI) on operational and financial performance within Malaysia's health supplement industry, focusing specifically on Bioalpha Holdings Berhad. The study addresses the critical issue of how integrated supply chain processes contribute to business efficiency and strategic positioning in a rapidly evolving market environment. Employing a qualitative case study approach, the research included in-depth interviews and observations with executives and supply chain professionals at Bioalpha. These interviews were analyzed using ATLAS.ti to systematically identify themes related to the influence of SCI on business operations. The research reveals that SCI significantly enhances operational efficiencies, reduces operational costs, and heightens market responsiveness, leading to improved financial performance and a strengthened competitive position. The study underscores that strategic supply chain management, supported by detailed data analysis through ATLAS.ti, is crucial for firms operating in volatile markets and facing intense competition. The thesis contributes to the field of supply chain management by elucidating the benefits of integration strategies in enhancing operational and financial outcomes. In an attempt to recommendation to improve supply chain integration capability, and based on findings, the researcher has proposed PrICE model, with an acronym for Brand Positioning, Integrated Information and Capability Expansion. This model represents the novelty of the study. The findings provide valuable insights for industry practitioners seeking to utilize SCI for competitive advantage and for researchers interested in the intersections of supply chain practices and business performance.